The Relationship between customers satisfaction and hybrid apparel retailing in Metro Manila - Montemayor, Levy Joy B.; Myers, Jason L.; Panlilio, Russell D.; Panoy, Dailyn Grace L.; Raviz, Ysabelle R.; Rivato, Khristine P.; Roxas, Beatriz Grace L.; San Diego, Caleb V.; Santiago, Mitziel Nathalie 4 0 16; 5
ABSTRACT: The COVID-19 pandemic has profoundly impacted brick-and-mortar stores, especially for small businesses, resulting in many turning into a hybrid business model that combines online and in-person sales. Hybrid sellers should prioritize forming customer-centric operations to make their business grow. So, this study investigates the different customer relationship management and customer satisfaction index factors and their correlation to the overall satisfaction derives from shopping in a hybrid business. The method used for this study is Quantitative, specifically the Correlational design, as study's objective is to analyze the association of different variables with overall customer satisfaction. The researchers gathered data through an online survey given to the customers who had experienced shopping on both online and offline channels-making the sampling technique of this study to be Purposive. The researchers used to the Pearson Correlation Coefficient to the test the hypotheses. Results showed that Customer Relationship Management Factors such as Awareness, Trust, Perceived Risk, Convenience, Control, Support, and Personalization positively correlate with customer satisfaction. Similarly, the Customer Satisfaction Indexes, namely Perceived Value, Perceived Quality, and Customer Expectations, have a positive relationship with overall customer satisfaction. Also, through the use of ANOVA, the researchers discovered that there is no significant difference in customer satisfaction when grouped according to demographic profile, except when grouped according to age, in which the results showed a significant difference. Keywords: Hybrid, Retailing, Clothing, Customer Relationship, Satisfaction
Research Study: (BSBA major in Operations Management) - Pamantasan ng Lungsod ng Maynila, 2023
Keywords: 2 -- 0; 6; 20; 20; 2